Persistent organochlorine pesticide residues in feed and fodder as a potential source of contamination in food of animal origin - NAG, SUBIR KUMAR; SINGH, ARPANA; SINGH, SULTAN (The Indian Journal of Animal Sciences, 2014)
The presence of varying types of toxic substances in feed and fodder is undesirable as from there they enter into the animal body system and redistribute themselves in different tissues and deposited there for a long time depending on nature of the toxicant. Residues of pesticides like organochlorines (OC) are often found in feed and fodder originating from different sources. Ultimately, these residues are transferred through the food chain and bioaccumulated in human body. The objective of the study was to investigate the extent and level of contamination in commonly used feed and fodder collected from different places with organochlorinated pesticide (OCP) residues. The results revealed that 34.6% of 318 samples were positive with residues of targeted OCPs. While hexachlorocyclohexane (HCH) residues were detected in 26.73% samples, endosulfan and dichlorodiphenyltrichloroethane (DDT) residues were found present in 11.95 and 11.64% samples respectively. Dicofol could be found in only 3 samples. In terms of concentration only 3.14 to 2.2% samples exceeded the limiting values of HCH and DDT respectively. Rest of the samples were either free or were contaminated al a level below limiting value. Endosulfan residues were present at a very low level (3–22 ppb). So, in terms of concentration and percentage of positive samples exceeding the limiting value of respective pesticides it can be concluded that the feed and footers can be considered as safe so far as OCP residues were concerned.